2006
DOI: 10.1111/j.1556-4029.2005.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the AmpFℓSTR® Yfiler™ PCR Amplification Kit: A Male Specific, Single Amplification 17 Y‐STR Multiplex System*

Abstract: In the past 5 years, there has been a substantial increase in the use of Y-short tandem repeat loci (Y-STRs) in forensic laboratories, especially in cases where typing autosomal STRs has met with limited success. The AmpFlSTR Yfiler PCR amplification kit simultaneously amplifies 17 Y-STR loci including the loci in the "European minimal haplotype" (DYS19, DYS385a/b, DYS389I, DYS389II, DYS390, DYS391, DYS392, and DYS393), the Scientific Working Group on DNA Analysis Methods (SWGDAM) recommended Y-STR loci (DYS43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
119
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(127 citation statements)
references
References 36 publications
4
119
3
1
Order By: Relevance
“…Paternity was confirmed by the paternity index value of 5.2 Â 10 3 for 45A and 2.6 Â 10 3 for 52A in the Asian population when the mothers' alleles are included. Thus far, in the four other published studies describing mutation rates with the 17 Yfiler loci [5][6][7][8] there have been no reports of a double mutation or a two repeat loss within a single father/son sample pair. However, previous studies involving fewer Y-STR loci have identified more than one mutation in a father/son pair.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Paternity was confirmed by the paternity index value of 5.2 Â 10 3 for 45A and 2.6 Â 10 3 for 52A in the Asian population when the mothers' alleles are included. Thus far, in the four other published studies describing mutation rates with the 17 Yfiler loci [5][6][7][8] there have been no reports of a double mutation or a two repeat loss within a single father/son sample pair. However, previous studies involving fewer Y-STR loci have identified more than one mutation in a father/son pair.…”
Section: Resultsmentioning
confidence: 99%
“…The paternity index (PI) value for sample pair 16B is 3.8 Â 10 7 in the African American population and for sample pair 101A is 5.5 Â 10 4 in the Asian population using the 15 autosomal Identifiler STR loci genotyping results. When the mothers' profile is included for sample pair 16B, the PI is 1.8 Â 10 9 and for 101A is 4.3 Â 10 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Y chromosome STR genotyping was conducted using the Yfiler PCR Amplification kit (Applied Biosystems, Foster City, CA, USA), 10 which co-amplifies a total of 17 Y chromosome STRs (DYS19, DYS385a,b, DYS389I, DYS389II, DYS390, DYS391, DYS392, DYS393, DYS437, DYS438, DYS439, DYS448, DYS456, DYS458, DYS635 and GATAH4). Further information on the loci can be found on the YHRD and NIST webpages (www.yhrd.org; www.cstl.nist.gov/strbase/y_strs.htm).…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…However, reliable locus-specific mutation rates are needed to carefully choose loci to minimize the error rate in kinship analysis and sample identification 2 while obtaining the maximum discriminatory power (eg, Mulero et al, Lim et al and Vermeulen et al [3][4][5]. Also in population genetics and evolutionary studies, correct inferences on the timing of major demographic events, the age of the most common ancestor, as well as dating Y-lineages and tracing disease evolution are based on the knowledge of mutation rates (eg, Shi et al, Zerjal et al and Xue et al [6][7][8] ).…”
Section: Introductionmentioning
confidence: 99%